Implementation of Smart Pop Up Book Media to Improve Read-Write Literacy in Children - St. Marwiyah; Ismail Ismail; Masruddin Masruddin (Institut Agama Islam Negeri Palopo, 2023)
Literacy improvement is a crucial task that is carried out in both schools and homes, or lingkungan. This is how the government was informed through the national literary festival. Using interactive media can help with literary event execution. Currently, children are becoming more interested in contemporary media or games like smartphones, tablets, and other devices of that nature. However, if children are not aware of their peers' sex, a variety of media might be harmful to them. Due to this, educators conducted media savvy pop-up book evaluations to promote early literacy in children. The purpose of this paper is to understand how to create a media smart pop-up book program for teaching children to read. Based on the mosque, this study was conducted on children aged 7 to 12 in Buntu Batu, Kecamatan Bastem, Kabupaten Luwu, and Sulawesi Selatan. The current study used a kualitatif deskriptif design for qualitative research. The study's findings are based on the development of young children's language literacy, which can improve when using media such as smart pop-up books during instruction. In light of this, it is evident that media smart pop-up books may be used to teach young children and assist them in developing their reading abilities.